The eleven deadliest sins of knowledge management - Fahey, Liam (California management review)
This article draws attention to a number of errors that could potentially cripple the efforts of any organization attempting to generate and leverage knowledge. Many of these errors are associated with the concept of knowledge itself-how knowledge is understood in organizational settings. The article notes the sources of each error as well as some key implications for managing knowledge. It concludes with some brief suggestions on how to avoid, or at least ameliorate these errors.